2019
DOI: 10.12688/f1000research.17407.1
|View full text |Cite
|
Sign up to set email alerts
|

Recent advancements in penile prosthetics

Abstract: Since the original inflatable penile prosthesis in the 1970s, several enhancements to penile prosthesis implant design, implant surgical technique, and post-operative care have been developed to increase overall patient (and partner) satisfaction rates. We, in this communication, seek to discuss these advancements and the overall impact in combating erectile dysfunction. As we continue to pursue avenues of effective and definitive treatment modalities for erectile dysfunction refractory to medical therapy, rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 39 publications
(40 reference statements)
0
1
0
Order By: Relevance
“…Both self and partner-reported satisfaction rates are evaluated to assess the outcomes. It has been shown that implantation of inflatable penile prosthesis brings more patient and partner satisfaction than medication therapy with PDE5 inhibitors or intracavernosal injections [22]. Satisfaction rates are reported to be higher with inflatable rather than malleable implants.…”
Section: Penile Prosthesismentioning
confidence: 99%
See 3 more Smart Citations
“…Both self and partner-reported satisfaction rates are evaluated to assess the outcomes. It has been shown that implantation of inflatable penile prosthesis brings more patient and partner satisfaction than medication therapy with PDE5 inhibitors or intracavernosal injections [22]. Satisfaction rates are reported to be higher with inflatable rather than malleable implants.…”
Section: Penile Prosthesismentioning
confidence: 99%
“…Nevertheless, PPI is costly, traumatic, and prone to complications, such as prosthetic infection, pump migration, automatic inflation, secondary surgery, etc. This is the main reason why it cannot become a first-line treatment [22].…”
Section: Penile Prosthesismentioning
confidence: 99%
See 2 more Smart Citations
“…The 5 and 10-year overall survivals of modern prosthetics are estimated to be 90.4% and 86.6%, respectively. 26 , 58 , 59 Given IPP placement to be a more invasive treatment, there are several adverse effects including severe infection, device erosion or extrusion, mechanical failure, and changes in penile length. A penile prosthetic is considered an irreversible procedure typically reserved for patients who fail pharmaceuticals and VED.…”
Section: Penile Rehabilitation Interventionsmentioning
confidence: 99%